Discrepancies in fighting strategies between Taekwondo medalists and non-medalists - Kwok, H. H. M. (Journal of Human Sport & Exercise, 2012)
The aim of this study was to compare the fighting strategies between medalists and non-medalists in Taekwondo. A total of 107 matches from the 16th Asian Games had been video-taped for notational analysis. Round house kick was the most frequently used kick by the medalists in the competition (63.29 %) while cut down kick (9.26 %) and push kick (7.08 %) were ranked second and third respectively. Aggressive mode of attack was the dominant fighting strategy used by the medalists (63.17 %). Discrepancies in fighting strategies between Taekwondo medalists and non-medalists were found in this study including mode of attack, use of turning attack, and number of types of kick employed.